Silicon Carbide Supported Palladium‐Iridium Bimetallic Catalysts for Efficient Selective Hydrogenation of Cinnamaldehyde. Issue 4 (18th February 2020) - Li, Penghui; Wang, Yingyong; Wang, Yunwei; Jin, Guoqiang; Guo, Xiang‐Yun; Tong, Xili
Summary of main observation and conclusion: Selective hydrogenation of α, β‐unsaturated carbonyls into saturated carbonyls is important to obtain remunerative products. However, it is still a challenge to achieve high activity and selectivity under mild conditions. Herein, Pd, Ir and bimetallic Pd‐Ir nanoparticles were uniformly deposited with high dispersity on the surface of SiC by a facile impregnation method, respectively. The as‐prepared Pd/SiC catalysts efficiently hydrogenate cinnamaldehyde to hydrocinnamaldehyde at room temperature and atmospheric pressure, and the activity of Pd/SiC is observed further enhanced by adding Ir component (conversion of 100%). In addition, the dependence of Pd‐Ir catalyst activity on Pd/Ir molar ratio confirms a synergistic effect between Ir and Pd, which originates from the electron transfer between Pd and Ir. Abstract :